Maternal endocrine adaptation throughout pregnancy to nutritional manipulation: consequences for maternal plasma leptin and cortisol and the programming of fetal adipose tissue development - Bispham, J; Gopalakrishnan, G S; Dandrea, J; Wilson, V; Budge, H; Keisler, D H; Broughton Pipkin, F; Stephenson, T; Symonds, M E (Endocrinology (Philadelphia), 2003)
Maternal nutrient restriction at specific stages of gestation has differential effects on fetal development such that the offspring are programmed to be at increased risk of adult disease. We investigated the effect of gestational age and maternal nutrition on the maternal plasma concentration of leptin and cortisol together with effects on fetal adipose tissue deposition plus leptin, IGF-I, IGF-II ligand, and receptor mRNA abundance near to term. Singleton bearing ewes were either nutrient restricted (NR; consuming 3.2-3.8 MJ/d of metabolizable energy) or fed to appetite (consuming 8.7-9.9 MJ/d) over the period of maximal placental growth, i.e. between 28 and 80 d gestation. After 80 d gestation, ewes were either fed to calculated requirements, consuming 6.7-7.5 MJ/d, or were fed to appetite and consumed 8.0-10.9 MJ/d. Pregnancy resulted in a rise in plasma leptin concentration by 28 d gestation, which continued up to 80 d gestation when fed to appetite but not with nutrient restriction. Plasma cortisol was also lower in NR ewes up to 80 d gestation, a difference no longer apparent when food intake was increased. At term, irrespective of maternal nutrition in late gestation, fetuses sampled from ewes NR in early gestation possessed more adipose tissue, whereas when ewes were fed to appetite throughout gestation, fetal adipose tissue deposition and leptin mRNA abundance were both reduced. These changes may result in the offspring of NR mothers being at increased risk of obesity in later life.